1992
DOI: 10.1017/s0022029900030314
|View full text |Cite
|
Sign up to set email alerts
|

SDS-solubilized whole-cell protein patterns ofStreptococcus salivariussubsp.thermophilusandLactobacillus delbrueckiisubsp.bulgaricusisolated from Greek yogurts

Abstract: SDS-solubilized whole-cell protein patterns of Streptococcus salivarius subsp. thermophilus and Lactobacillus delbrueckii subsp. bulgaricus isolated from Greek yogurts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Streptococcus thermophilus growth is known to be stimulated by the bioavailability of free amino acids and peptides present within the milk, released due to the proteolytic activity of L. bulgaricus (Tamime et al, 2007). Also, L. bulgaricus is stimulated by S. thermophilus in symbiotic fermentation (Zourari, Commissaire & Desmazeaud, 1992). Since the growth patterns of L. bulgaricus in control yogurt compared to yogurt with W 1 /O/W 2 emulsion were similar it was indicated that the symbiosis during acidification was not interrupted by the W 1 /O/W 2 emulsion.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Streptococcus thermophilus growth is known to be stimulated by the bioavailability of free amino acids and peptides present within the milk, released due to the proteolytic activity of L. bulgaricus (Tamime et al, 2007). Also, L. bulgaricus is stimulated by S. thermophilus in symbiotic fermentation (Zourari, Commissaire & Desmazeaud, 1992). Since the growth patterns of L. bulgaricus in control yogurt compared to yogurt with W 1 /O/W 2 emulsion were similar it was indicated that the symbiosis during acidification was not interrupted by the W 1 /O/W 2 emulsion.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…bulgaricus and Streptococcus salivarius subsp. thermophiles [10], and there are countless protected strains that have been developed for industrial use [11, 12]. In addition to these starter cultures, some products employ additional species or strains to impart particular health benefits.…”
Section: Methods Of Fermentationsmentioning
confidence: 99%
“…T h e maintenance of pLZ15 and expression of P-gal activity were tested by serially transferring transformants in G-M17 broth for 100 generations, plating them on X-Gal G-M17 agar and determining the ratio of white/blue colonies. The protein pattern of SDSsolubilized whole-cells was analysed according to Zourari et al (1992). T h e carbohydrate degradation pattern of the strains was determined using enzymatic test strips containing 48 substrates (API 50CH, Bio-Merieux, Marcy l'Etoile, France).…”
Section: Southern Blot Hybridization and Expression Of The !-Gal Genementioning
confidence: 99%